Development of GALARAMA Learning Media in Natural and Social Sciences (IPAS) to Enhance the Learning Activeness of Fourth-Grade Students at MI As-Salam Bogo Nglawak Kertosono, Nganjuk - Vanie Suryaningrum; Zainul Anwar (PGMI, STAI Miftahul Ula Nganjuk, 2025)
The development of GALARAMA learning media for Grade IV IPAS (Natural and Social Sciences) on the topic Building a Civilized Society at MI As-Salam Bogo Nglawak Kertosono Pecuk is based on a phenomenon observed at the school, namely the suboptimal use of learning media. This condition occurs because teachers still frequently rely on lecture-based teaching methods in daily classroom activities. The objectives of this study are: (1) to develop GALARAMA learning media for IPAS instruction on the topic Building a Civilized Society for Grade IV students at the SD/MI level; and (2) to determine the effectiveness of GALARAMA learning media in IPAS instruction on the same topic. This study employs a Research and Development (R&D) approach. The development model used refers to the 4-D model proposed by Thiagarajan, which consists of four stages: (1) Define, (2) Design, (3) Develop, and (4) Disseminate. Data collection instruments included validation questionnaires administered to media experts and subject-matter experts, as well as pretest and posttest instruments given to students to measure the effectiveness of the developed product. The data analysis technique used was quantitative data analysis to assess the validity and effectiveness of the product. The result of this research and development is a learning media product named GALARAMA. Product validation conducted by material experts and media experts obtained an overall average percentage score of 87%, indicating that the product is valid. Furthermore, the results of the pretest and posttest analysis showed an N-gain score of 0.63 or 63.4%. These results indicate that the developed product falls into the “moderate” score category with a level of effectiveness classified as “moderately effective,” and it is proven to be capable of improving student learning activeness.